The Genotoxic Potential of Organic Emissions from Domestic Boilers Combusting Biomass and Fossil Fuels - Sikorova, Jitka; Hopan, Frantisek; Kubonova, Lenka; Horak, Jiri; Milcova, Alena; Rossner, Pavel; Ambroz, Antonin; Krpec, Kamil; Molchanov, Oleksandr; Zavodna, Tana (Toxics, 2025)
Solid fuels are still widely used in household heating in Europe and North America. Emissions from boilers are released in proximity to people. Therefore, there is a need to minimise the toxicity of emissions affecting human health to the greatest extent possible. This study compares the genotoxic potential of the emissions of four boilers of modern and old design (automatic, gasification, down-draft, over-fire) operating at reduced output to simulate the real-life combustion fed by various fossil and renewable solid fuels (hard coal, brown coal, brown coal briquettes, wood pellets, wet and dry spruce). Organic emissions were tested for genotoxic potential by analysing bulky DNA adducts and 8-oxo-dG adduct induction. There was no consistent genotoxic pattern among the fuels used within the boilers. Genotoxicity was strongly correlated with polycyclic aromatic hydrocarbon (PAH) content, and even stronger correlation was observed with particulate matter (PM). In all measured variables (PM, PAHs, genotoxicity), the technology of the boilers was a more important factor in determining the genotoxic potential than the fuels burned. The highest levels of both bulky and 8-oxo-dG DNA adducts were induced by organics originating from the over-fire boiler, while the automatic boiler exhibited genotoxic potential that was ~1000- and 100-fold lower, respectively.
Keywords: polycyclic aromatic hydrocarbons; domestic heating; genotoxicity; 8-oxo-dG; DNA adducts; particulate matter